2008
DOI: 10.1002/mds.22143
|View full text |Cite
|
Sign up to set email alerts
|

Familial Parkinsonism with digenic parkin and PINK1 mutations

Abstract: To clarify the genetic correlation between parkin and PINK1, we screened for PINK1 mutations in 175 parkinsonism patients with parkin mutations. We detected two sibling pairs and one sporadic patient carrying both parkin and PINK1 mutations. The age at onset of Parkinsonism of patients with the digenic mutations was lower than that of patients with the same parkin mutation alone. In addition, two of three patients carrying both parkin and PINK1 mutations had schizophrenia. These findings indicate that PINK1 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Auditory hallucination in schizophrenia is related to higher functional connectivity between hippocampal complex and thalamus and increased dopaminergic transmission [4]. In contrast, the main brunt of dopaminergic denervation in PD is in the motor striatum [1,2]. Therefore, even though schizophrenia and Parkin disease have opposing dopamine pathophysiologies, dopaminergic dysfunction in different parts of the striatum may explain why PD and schizophrenia may occur simultaneouly [2,5].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Auditory hallucination in schizophrenia is related to higher functional connectivity between hippocampal complex and thalamus and increased dopaminergic transmission [4]. In contrast, the main brunt of dopaminergic denervation in PD is in the motor striatum [1,2]. Therefore, even though schizophrenia and Parkin disease have opposing dopamine pathophysiologies, dopaminergic dysfunction in different parts of the striatum may explain why PD and schizophrenia may occur simultaneouly [2,5].…”
Section: Discussionmentioning
confidence: 94%
“…The reported psychiatric symptoms in Parkin disease are depression, autism, anorexia nervosa, suicidal idea, paranoid, panic attack and hallucination [1]. Parkin and PTEN-induced putative kinase 1 (PINK1) combined mutations could induce psychiatric disorders because of mitochondrial dysfunction [2]. Parkinson's disease (PD) is a disorder of decreased striatal dopaminergic innervations, whereas schizophrenia is believed to be due to dopamine overactivity in cortico-striatal-thalamo-cortical loop in the mesolimbic system [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such heterozygous mutations in recessive PD genes may modify the phenotype in patients with mutations in other PD genes (Klein et al 2007;Funayama et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Funayama et al identified PD patients carrying both parkin and PINK1 mutations, whose onset age was younger than that of patients with the same parkin mutation alone. The presence of digenic mutations, such as parkin plus PINK1 mutations, suggests that a PINK1 mutation could influence the clinical symptoms of parkin-linked PD (Funayama et al 2008). However, Kitada and colleagues (Kitada et al 2009) reported that triple knockout of Parkin, PINK1, and DJ-1 resulted in normal morphology and numbers of dopaminergic and noradrenergic neurons in the substantia nigra and locus coeruleus.…”
Section: Pink1/parkin Pathwaymentioning
confidence: 99%